Intravital Ca²⁺ imaging of pancreatic β cell function after bariatric surgery - Tröster, Philip (2022)
Bariatric surgery has long become an appropriate and common treatment for patients with severe obesity and many related conditions such as type 2 diabetes. However, the exact mechanism leading to improved metabolism shortly after surgery, most notably independent of weight loss, has not yet been fully elucidated. Akalestou's recent publication, "Intravital imaging of islet Ca2+ dynamics reveals enhanced β cell connectivity after bariatric surgery in mice," provides the first detailed insight into the progression of pancreatic islet function after bariatric surgery. By transplanting pancreatic islets equipped with a genetically encoded calcium indicator into the anterior chamber of the eye, improvements in Ca2+ dynamics and a more potent β cell network were observed over an extended time course after the surgical procedure. In the following sections, we will take the opportunity to briefly outline the association between bariatric surgery and diabetes, highlight the issue of anesthesia during intravital Ca2+ imaging, and finally comment on some biological relationships related to β cell function.